Deleterious somatic variants in 473 consecutive individuals with ovarian cancer: results of the observational AGO-TR1 study (NCT02222883). Issue 9 (12th April 2019) - Hauke, Jan; Hahnen, Eric; Schneider, Stephanie; Reuss, Alexander; Richters, Lisa; Kommoss, Stefan; Heimbach, André; Marmé, Frederik; Schmidt, Sandra; Prieske, Katharina; Gevensleben, Heidrun; Burges, Alexander; et al.
Abstract : Background: For individuals with ovarian cancer (OC), therapy options mainly depend on BRCA1/2 germline status. What is the prevalence of deleterious somatic variants, that is, does genetic tumour testing identify subgroups of individuals who also might benefit from targeted therapy? Methods: Paired analysis of tumour-derived versus blood-derived DNA to determine the prevalence of deleterious somatic variants in OC predisposition genes ( ATM, BRCA1/2, BRIP1, MSH2/6, PALB2, RAD51C/D and TP53 ) and the PIK3CA and PTEN genes in individuals with OC (AGO-TR1 study, NCT02222883 ). Results were complemented by BRCA1, PALB2 and RAD51C promoter methylation analyses and stratified by histological subtype; 473 individuals were included. Results: The combined analyses revealed that deleterious germline variants in established OC predisposition genes (all: 125/473, 26.4%; BRCA1/2 : 97/473, 20.5%), deleterious somatic variants in established OC predisposition genes excluding TP53 (all: 39/473, 8.2%; BRCA1/2 : 30/473, 6.3%) and promoter methylation (all: 67/473, 14.2%; BRCA1 : 57/473, 12.1%; RAD51C : 10/473, 2.1%; PALB2 : 0/473) were mutually exclusive, with a few exceptions. The same holds true for deleterious somatic PIK3CA and/or PTEN variants (33/473, 7.0%) found to be enriched in endometrioid and clear cell OC (16/35, 45.7%); 84.3 % of the deleterious single-nucleotide/indel germline variants in established OC predisposition genes showed significantly higher variant fractions (VFs) in the tumour-derived versus blood-derived DNA, indicating a loss of the wild-type alleles. Conclusion: Tumour sequencing of the BRCA1, BRCA2, PIK3CA and PTEN genes along with BRCA1 and RAD51C promoter methylation analyses identified large subgroups of germline mutation-negative individuals who may be addressed in interventional studies using PARP or PI3K/AKT/mTOR inhibitors. Trial registration number: NCT02222883